2018
DOI: 10.1097/md.0000000000010794
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of multisite hemorrhage by several methods in brain metastasis of choriocarcinoma

Abstract: The diagnosis of choriocarcinoma may be difficult, especially in the setting with the limit of medical resources. The application of various diagnostic techniques such as x-ray, computed tomography, and magnetic resonance imaging is helpful for evaluating the patient's condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Choriocarcinoma has a markedly tendency of early metastasis, just like what we found in this case, although vaginal bleeding is the common symptom of choriocarcinoma. [ 5 ] In this case presenting no vaginal bleeding, but spinal oppressive symptoms, the spine metastases were very rare compares to common lung metastases. [ 6 , 7 ] Table 1 presents all cases of reported choriocarcinoma metastases to the spine up to date.…”
Section: Discussionmentioning
confidence: 94%
“…Choriocarcinoma has a markedly tendency of early metastasis, just like what we found in this case, although vaginal bleeding is the common symptom of choriocarcinoma. [ 5 ] In this case presenting no vaginal bleeding, but spinal oppressive symptoms, the spine metastases were very rare compares to common lung metastases. [ 6 , 7 ] Table 1 presents all cases of reported choriocarcinoma metastases to the spine up to date.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of brain metastasis is approximately 8.8-66.7% [2][3][4]. Some studies have reported the occurrence of intracranial hemorrhage [5][6][7] and subarachnoid hemorrhage after the formation of aneurysms due to the vascularity of the lesion [8][9][10]. Furthermore, when rebleeding occurs, the outcome is even poorer [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of brain metastasis of choriocarcinoma is relatively high [2][3][4]. Because of its vascularity, there have been some reports of cerebral hemorrhage and aneurysm formation related to brain metastasis of choriocarcinoma [5][6][7][8][9][10]. Furthermore, when rebleeding occurs, the outcome is even worse [10], and early diagnosis and treatment are extremely important to achieve a good outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of choriocarcinoma with brain metastasis is dangerous and is the leading cause of death. They are usually accompanied by lung metastasis or vaginal metastasis [6].The initial stage of metastasis is mostly asymptomatic. Brain metastasis is divided into 3 stages.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Choriocarcinoma is highly malignant and metastasizes early. Before the advent of chemotherapy drugs, the mortality rate was over 90% [2,3].The primary treatment method of choriocarcinoma is chemotherapy [5,6]. The appropriate plan is determined by staging and grading, and the comprehensive treatment of surgery and radiotherapy is appropriately coordinated.…”
Section: Discussion/conclusionmentioning
confidence: 99%